Hypersexual disorder and recidivism risk in individuals convicted of sexual offenses - Gregório Hertz, Priscilla (The journal of forensic psychiatry & psychology, 2022)
Hypersexual disorder (HD) is characterized by an excessively increased frequency and intensity of sexual fantasies, urges, or behaviors and is a recidivsm risk factor for sexual offenses. The present study examined the relevance of HD in predicting sexual recidivism using previously proposed diagnostic criteria for DSM-5. First, we investigated the prevalence of HD in a sample of 418 adult men incarcerated for sexual offenses. Second, by using a follow-up period of M = 11.07 years (SD = 1.86), the accuracy of the HD criteria in predicting general sexual, contact sexual and violent recidivism was examined. Finally, the incremental predictive validity of HD beyond the Static-99 and the Stable-2007 was calculated. The proposed DSM-5 criteria were fulfilled by 6.6% of the sample. HD and two of its five diagnostic criteria exhibited significant correlations with sexual recidivism. A small significant predictive accuracy for contact sexual recidivism (AUC = .614) was found, which increased when a sum score of the five diagnostic criteria was used (AUC = .652). Finally, the HD sum score showed incremental predictive validity beyond the joint Static-99 and Stable-2007. Therefore, a more specific understanding of hypersexuality can contribute to risk management in the context of sexual (re-)offending.